2020
DOI: 10.1002/ijfe.2085
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and global business performance

Abstract: This paper contributes to the literature on business performance by investigating the relationship between terrorism and global business performance at country level. A measure of a country's distance from the frontier score of the World Bank's Doing Business index is used to proxy for business performance. The results of the fixed-effects estimations based on 173 countries over 7 years (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) show that terrorism has no significant relationship with global busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…These results align with the ongoing debate regarding the economic consequences of terrorism. Previously research reported that terrorism negatively impacts a country's economic conditions by drastically impacting business conditions (Tauringana et al, 2021).…”
Section: Baseline Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These results align with the ongoing debate regarding the economic consequences of terrorism. Previously research reported that terrorism negatively impacts a country's economic conditions by drastically impacting business conditions (Tauringana et al, 2021).…”
Section: Baseline Regression Analysismentioning
confidence: 99%
“…Previous research reported that poorly performing firms and unsuccessful businesses lead to higher unemployment rates lowering the opportunity cost to participate in terrorism activities (Gurbuz & Aybars, 2010;Iqbal & Usman, 2018;Mansoor et al, 2022). Hence, researchers have highlighted the significance of examining the association of poor firm performance with terrorism (Tauringana et al, 2021).…”
Section: Robustness Analysismentioning
confidence: 99%
“…In Turkey, North Africa and the Near East, terrorist activities continue, and travellers prefer to choose some other destinations instead of these, in which the safety situation is currently unstable. In Europe also, there were several terrorist attacks, namely in Brussels, Berlin and Nice, and the migrant crisis continues following the large migrant wave back in 2015 (Mawby et al, 2021;Tauringana et al, 2020). The emergence of the pandemic caused by COVID-19 has had a big impact on the reduction in tourist trends, which will cause long-term consequences for economies and tourism throughout the world.…”
Section: Contemporary Trends In the Hotel Distribution In Europe Theoretical Backgroundmentioning
confidence: 99%
“…Other arguments put forward by studies (see, Chen and Siems, 2004; Tingbani et al. , 2019; Tauringana et al. , 2021) are that terrorism impedes the ability of firms to perform productively by destroying business infrastructures and imposing fear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of actual incidents of terrorism, and the comprehensive analysis of firms, will provide much detailed information on how an objective type of instability affects the performance of firms. Second, unlike most studies on terrorism (such as Powers and Choi, 2012; Singh, 2013; Efobi and Asongu, 2016), we have added to the very few existing studies that have used the severity of terror attacks – which is the number of fatalities and people injured (see, Mazhar, 2019; Tauringana et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%